2017
DOI: 10.1155/2017/6720594
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells in Myeloid Malignancies: A Focus on Immune Escaping and Therapeutic Implications

Abstract: The importance of the bone marrow microenvironment forming the so-called niche in physiologic hemopoiesis is largely known, and recent evidences support the presence of stromal alterations from the molecular to the cytoarchitectural level in hematologic malignancies. Various alterations in cell adhesion, metabolism, cytokine signaling, autophagy, and methylation patterns of tumor-derived mesenchymal stem cells have been demonstrated, contributing to the genesis of a leukemic permissive niche. This niche allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 147 publications
0
20
0
1
Order By: Relevance
“…Complete haplotype loss is seen in patients who relapse following haploidentical transplants and can occur in up to one third of these patients . The microenvironment of the bone marrow niche may protect malignant cells from immune surveillance or death from cytotoxic agents . Furthermore, reduced intensity and NMA conditioning may not suppress aggressive disease enough to allow GVL to develop, especially in the setting of MRD .…”
Section: Introductionmentioning
confidence: 99%
“…Complete haplotype loss is seen in patients who relapse following haploidentical transplants and can occur in up to one third of these patients . The microenvironment of the bone marrow niche may protect malignant cells from immune surveillance or death from cytotoxic agents . Furthermore, reduced intensity and NMA conditioning may not suppress aggressive disease enough to allow GVL to develop, especially in the setting of MRD .…”
Section: Introductionmentioning
confidence: 99%
“…14 (ii) The number of minor histocompatibility antigens (mHA) as the primary targets of GVL effects 15 is continuously increasing (now over 50) 16. Some mHAs are preferentially expressed by the hematopoietic system, and T cells may target them as self- or allo-restricted peptide.…”
Section: Role Of Microenvironmentmentioning
confidence: 99%
“…The bone marrow microenvironment seems to be ideal for this approach since it constitutively expresses MHC Class II on stromal cells. 26 Considering the crucial role of the microenvironment for leukemic cell survival and escape 14 , it is obvious that targeting cancer stroma could be used to eradicate residual cancer cells. Destroying the stromal bone marrow microenvironment in which the leukemia cells reside would be restricted to the immediate vicinity of the cancer cells.…”
Section: Role Of Microenvironmentmentioning
confidence: 99%
“…This results in a diminished cell cycle activity of HSPCs cultured on MDS-MSCs, highlighting that impaired stromal support contributes to ineffective hematopoiesis [98,112,113]. Moreover, several studies demonstrated an altered immunomodulatory function of MDS-MSCs, affecting tumor immune surveillance [114]. Evidence to date suggests that MSCs from neoplastic niche are educated to polarize macrophage toward an M2, anti-inflammatory, phenotype and they are responsible for increase Treg through the secretion of indoleamine 2,3-dioxygenase (IDO).…”
Section: Mscs In Hematological Malignanciesmentioning
confidence: 99%